A case of possible atypical demyelinating event of the central nervous system following COVID-19 - Zoghi, Anahita; Ramezani, Mahtab; Roozbeh, Mehrdad; Darazam, Ilad Alavi; Sahraian, Mohammad Ali (Multiple sclerosis and related disorders, 2020)
•Clinical awareness of physicians about neurological complications of COVID-19 decreases the mortality rate among infected people.•Neurological presentation of COVID-19 infection categorized into two groups of symptoms of the central nervous system (CNS) and of the peripheral nervous system (PNS).•Cytokine storm, a well-known immune reaction to this specific viral infection, can cause inflammation and central nervous system (CNS) tissue axonal or demyelinating damage.•Our patient had a central demyelinating brain injury following COVID-19 infection. After the novel coronavirus disease outbreak first began in Wuhan, China, in December 2019, the viral epidemic has quickly spread across the world, and it is now a major public health concern. Here we present a 21-year-old male with encephalomyelitis following intermittent vomiting and malaise for 4 days. He reported upper respiratory signs and symptoms 2 weeks before this presentation. Two cerebrospinal fluid (CSF) analyses were notable for mononuclear pleocytosis, elevated protein (more than 100 mg/dl), and hypoglycorrhachia. Brain Magnetic Resonance Imaging (MRI) showed bilateral posterior internal capsule lesions extending to the ventral portion of the pons and a marbled splenium hyperintensity pattern. Cervical and thoracic MRI showed longitudinally extensive transverse myelitis (LETM), none of which were enhanced with gadolinium. Both the AQP4 and MOG antibodies were negative. Spiral chest computed tomography (CT) scan confirmed to COVID-19 as did the high IgG level against coronavirus, but the oropharyngeal swabs were negative. Neurological manifestations of COVID-19 have not been adequately studied. Some COVID-19 patients, especially those suffering from a severe disease, are highly likely to have central nervous system (CNS) manifestations. Our case is a post-COVID-19 demyelinating event in the CNS.